2020
DOI: 10.21147/j.issn.1000-9604.2020.04.09
|View full text |Cite
|
Sign up to set email alerts
|

No expenditure difference among patients with liver cancer at stage I-IV: Findings from a multicenter cross-sectional study in China

Abstract: Objective The number of liver cancer patients in China accounts for more than half of the world. However, China currently lacks national, multicenter economic burden data, and meanwhile, measuring the differences among different subgroups will be informative to formulate corresponding policies in liver cancer control. Thus, the aim of the study was to measure the economic burden of liver cancer by various subgroups. Methods A hospital-based, multicenter and cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Currently, the most common first-line treatment strategy is the use of interventional therapy, which could inject the anticancer drugs or embolization agents into the hepatic artery through femoral artery intubation, assisted by angiography, digital subtraction, and other imaging devices, thereby conducting a minimally invasive approach to the local lesions [ 1 ]. Recent developments in interventional therapy have highlighted the merits that it could repeat many times, effectively relieve the symptoms, and prolong the survival period [ 2 – 5 ]; however, the actual therapeutic effect largely depends on the treatment compliance [ 6 ]. In addition, previous research has revealed the poor clinical treatment effect associated with negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most common first-line treatment strategy is the use of interventional therapy, which could inject the anticancer drugs or embolization agents into the hepatic artery through femoral artery intubation, assisted by angiography, digital subtraction, and other imaging devices, thereby conducting a minimally invasive approach to the local lesions [ 1 ]. Recent developments in interventional therapy have highlighted the merits that it could repeat many times, effectively relieve the symptoms, and prolong the survival period [ 2 – 5 ]; however, the actual therapeutic effect largely depends on the treatment compliance [ 6 ]. In addition, previous research has revealed the poor clinical treatment effect associated with negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the 6 economic burden studies was heterogeneous ( Table 2 ). While 1 study relying on cancer registry claims data was regarded as having “strong” global rating ( 27 ), 2 studies based on hospital databases, social insurance information system, and national health insurance database were rated “moderate” ( 26 , 29 ), and another 3 studies based on survey and hospital electronic health records were rated “weak” ( 25 , 28 , 30 ). A discrepancy occurred and resolved in raters, and the reasons were differences in interpretation of criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Another hospital-based cross-sectional survey study covering 39 hospitals and 21 project sites in 13 provinces was carried out to investigate the economic burden of liver cancer in mainland China from 2012-2014 ( 28 ). Demographic and societal information, expenditures, and time loss due to clinical visits of 1,196 patients with HCC were investigated with the use of a structured questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, advances in treatment including surgical techniques, liver metastasis therapy, and targeted therapy remarkably improved survival rates of patients and prolonged their survival duration, which unavoidably added to the hospitalization expenditure of colorectal cancer currently ( 23 ). Early prevention strategies could help reduce the cancer expenditure in hospitals ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%